Foraging Behaviour of Honey bee (Apis mellifera) in Relation to Weather Parameters under Open Field Condition in Linseed Crop - Singh, Sandeep Kumar; Kumar, Ritesh; Chauhan, Saroj (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The present study entitled “Foraging Behaviour of Honey bee (Apis mellifera) in Relation to Weather Parameters Under Open Field Condition in Linseed crop” was carried out on Linseed variety “Sharda” at the Entomology research field situated at Heera Puri Research Farm, Institute of Agriculture and Natural Sciences, Deen Dayal Upadhyaya Gorakhpur University Gorakhpur, Uttar Pradesh during the Rabi season 2023- 2024. The linseed variety “Sharda” was sowing in the field using three replications with division 8 treatment including plot size (4m×3m2) by using randomized block design. The observation was started in morning (8000 h.) to evening (1700 h.) for conduct to understand the effect of weather parameters on the foraging intensity, foraging rate and foraging speed of Apis mellifera. The results revealed that the maximum foraging intensity was observed (11.57 bees/m2/minute) in 18th SW during the period of 1000-1200 hours whereas the minimum foraging intensity was observed (3.83 bees/m2/minute) in 13th SW during the time interval of 1500-1700 hours. However, the results were observed that the foraging rate has been maximum (10.51flowers/minute) in 16th SW during the period of 1000-1200 hours, whereas the minimum foraging rate was observed (3.76 flowers/minute) during the period of 1500- 1700 hours in 13th SW. Furthermore, the maximum foraging speed was observed (6.18 second/flower) in 18th SW during the period of 8000-1000 hours. Whereas the minimum time spend per flower was observed (1.02 second/flower) in 20th SW during the period of 1500- 1700 hours. The data revealed that the correlation coefficient of relative abundance, foraging rate and foraging speed of honey bee was positive correlated to the weather parameter (Tmax. & Tmin.) whereas the negative correlated with the relative humidity during (morning and evening) and rainfall.